2022
DOI: 10.1186/s12889-022-12512-6
|View full text |Cite
|
Sign up to set email alerts
|

Anemia prevalence, severity, types, and correlates among adult women and men in a multiethnic Iranian population: the Khuzestan Comprehensive Health Study (KCHS)

Abstract: Background Despite all recent health-related improvements, anemia remains an extensive global public health issue affecting the lives of about one-fourth of the world population in a geographically heterogeneous pattern. We, therefore, aimed to illustrate the prevalence, severity, most common types, and major determinants of anemia among adults in Khuzestan, Iran, from 2016 to 2019. Methods In a large population-based cross-sectional study comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
5
11
0
Order By: Relevance
“…In this finding, the sex of the study participants was significantly associated with the presence of anemia in which being female is stated to be a non-modifiable risk factor for the occurrence of anemia among CKD patients, yielding a similar result to a study carried out in Turkey [43], Malaysia [44], Italy [55], United States [56], and Iran [57]. This may be simply elucidated by the biological susceptibility of the inevitable blood loss at the time of menstruation and pregnancy in pre-menopausal women as well as dietary inadequacy [28,43].…”
Section: Plos Onesupporting
confidence: 77%
“…In this finding, the sex of the study participants was significantly associated with the presence of anemia in which being female is stated to be a non-modifiable risk factor for the occurrence of anemia among CKD patients, yielding a similar result to a study carried out in Turkey [43], Malaysia [44], Italy [55], United States [56], and Iran [57]. This may be simply elucidated by the biological susceptibility of the inevitable blood loss at the time of menstruation and pregnancy in pre-menopausal women as well as dietary inadequacy [28,43].…”
Section: Plos Onesupporting
confidence: 77%
“…In this survey, a significant association was found between gender and categorized hemoglobin and calcium. The hemoglobin level was classified as below and above 11.5, and it was observed that the hemoglobin level was much lower in women than in men; it seems that women suffer from anemia (23). Due to anemia, it seems that these children should be treated for anemia.…”
Section: Discussionmentioning
confidence: 99%
“…! Anaemia: classification of severity based on the WHO guidelines [ 25 ]. $ Low, normal, and high ranges for each biochemical parameter were classified based on the laboratory reference ranges ( , accessed on 5 September 2022).…”
Section: Figurementioning
confidence: 99%